Nasal Tip Reshaping in Orthognathic Surgery: A Novel Intraoral Minimally Invasive Approach - Santagata, Mario; Boschetti, Ciro Emiliano; Chagas-Junior, Otacilio Luiz; Gualdi, Alessandro; Rugge, Luigi; Tartaro, Gianpaolo; Chirico, Fabrizio (Facial Plastic Surgery, 2024)
Current concepts in orthognathic surgery focus on not just rectifying dentoskeletal irregularities but also improving facial aesthetic and function. In this respect, nasal reshaping holds extraordinary significance in determining surgery effectiveness and patient satisfaction. Facial preoperative evaluations emphasize the paramount functional and aesthetic impacts of caudal septum in tip reshaping. Deviations in this anatomical subunit could lead to significant nasal obstructions and aesthetic changes as twisted nasal tip, affecting projection, rotation, and columellar–alar relationship. These considerations are essential in orthofacial surgery, as maxillary movements might exacerbate or worsen preexisting nasal tip deformity. In this paper, we aim to describe a novel and innovative minimally invasive approach presenting a detailed account of a rhinoseptoplasty in which the entire nasal tip reshaping procedure was performed intraorally during orthognathic surgery. The technique focused on achieving optimal nasal tip projection and rotation, centering, and stabilization through strategic maneuvers such as incremental dissection of maxillary spine chondroperiosteal junction, superoposterior strut preservation, vertical and caudal septum resection, and anterior nasal spine tip support. Techniques including subnasal drilling and septal stabilization suture are detailed. Specific attention is given to addressing deficiencies in posterior septal angle and labiocolumellar relationship. Postoperative care is described and subjective evaluations were performed to assess patient and surgeon satisfaction with facial symmetry and overall aesthetic improvements. In our experience, the described approach offers valuable surgical finesse to orthognathic surgery, effectively targeting caudal septum deviations and nasal tip droopy. Its unique perspective enhances both functional and aesthetic results, particularly in the context of profiloplasty. No external nasal incision was performed and the totality of nasal tip reshaping was scarless and performed through an intraoral approach. Surgical precision in execution of this novel and tailored surgical approach has been shown to have a profound impact for enhancing outcomes of orthofacial surgery procedure.
Keywords: orthofacial surgery; orthognathic surgery; nasal tip drooping; rhinoplasty; minimally invasive approach